Symposium 1: Digital citizenship in teacher education – Exploring conceptualizations in a postdigital era - Örtegren, Alex (Proceedings of the International Conference on Networked Learning, 2024)
In a postdigital era, an increasingly important dimension of citizenship is digital citizenship, which is reflected for instance by digital civic engagement, fake news, and disinformation, not least during the Covid-19 pandemic. Teacher education (TE) prepares student teachers for the fostering of citizens in K-12 schools, and various conceptualizations of digital citizenship appear in educational research that could inform TE practice. This paper explores two common conceptualizations of digital citizenship in educational research, Ribble’s nine elements of digital citizenship and Choi’s four-category model, and critically examines how these reflect digital citizenship in a postdigital era, including potential implications for TE. The paper shows that neither conceptualization fully reflects digital citizenship in a postdigital era although Choi’s model mirrors some characteristics, for instance a blurredness between binaries such as “online” and “offline”, and a multi-faceted understanding of citizenship and digital technologies. Critically analyzing digital citizenship is important as the conceptualizations informing TE may impact the preparation of future teachers to teach for digital citizenship in a postdigital era.